Enhancing Student Motivation and Competencies: Integrating E-Learning, Technological Literacy, and Cultural Alignment - Shannaq, Boumedyen; Saleem, Imran; AlRawahi, Said; Almhlawi, Saad; AlMaqbali, Said (Ital Publication, 2025)
This study explores the integration of open innovation in education with a focus on technology and cultural aspects, aiming to foster improvements in educational management and policy within Oman learning environments. The research investigates the relationships between technological literacy (TL), cultural compatibility (CC), human face-to-face communication methods (HFtFCM), and student motivation and engagement (SMaE). A survey was conducted among 1,436 Oman students, and the data were analyzed using partial least squares and structural equation modeling to assess the moderating effects of TL and CC on these relationships. Results indicate that incorporating TL and CC as moderators significantly strengthens the mediation framework, enhancing the connection between HFtFCM and student perception of communication effectiveness (SPoCE). Specifically, the p-value decreased from 0.11 to 0.005, highlighting increased statistical significance, and the path from HFtFCM to SPoCE to SMaE improved from -0.051 to 0.071, demonstrating a stronger mediation effect. Conversely, the indirect effect from Technology-Based Communication Methods (TBCM) to SPoCE to SMaE decreased from 0.047 to 0.008. Additionally, notable paths such as TL → SPoCE and CC → SPoCE emerged, illustrating the enhanced explanatory power of these moderators. Conclusion: These findings underscore the potential of TL and CC to elevate student engagement and communication effectiveness, offering valuable insights for educational policy development and leadership programs. Doi: 10.28991/ESJ-2025-09-01-025 Full Text: PDF